Formal methods and software engineering : 16th International Conference on Formal Engineering Methods, ICFEM 2014, Luxembourg, Luxembourg, November 3-5, 2014. Proceedings - Pang, Jun; Merz, Stephan (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 16th International Conference on Formal Engineering Methods, ICFEM 2014, held in Luxembourg, Luxembourg, in November 2014. The 28 revised full papers presented were carefully reviewed and selected from 73 submissions. The papers cover a wide range of topics in the area of formal methods and software engineering and are devoted to advancing the state of the art of applying formal methods in practice. They focus in particular on combinations of conceptual and methodological aspects with their formal foundation and tool support.